What is the association between schoolwork-related anxiety and science literacy proficiency? A comparison between Southeast Asia and Northwest Europe - Grabau, Lawrence; Galand, Benoît; Lafontaine, Dominique; Lavonen, Jari; Ólafsson, Ragnar F.; Trudel, Louis; Yoon, SaeYeol (Frontiers in Education, 2024)
Abstract What is the shape of the association between schoolwork-related anxiety (SRA; sometimes referred to as “test anxiety”) and science literacy proficiency (SLP)? Prior results in some areas (e.g., Flanders) have showed an inverse linear relationship between SRA and SLP. Intriguingly, academic anxiety showed an inverse “U-shaped” association with academic performance in Taiwan. Data for six southeast Asian (SEA; Hong Kong, Japan, Korea, Macao, Singapore, Taiwan) and six northwest European (NWE; Belgium, Estonia, Finland, Iceland, Ireland, the Netherlands) nations/entities were drawn from PISA 2015, the most recent science-focused iteration of OECD’s (Organization for Economic Cooperation and Development) triennial PISA (Programme for International Student Assessment) evaluations. Mean SRA and SLP, respectively, were 0.34 and 532 across the selected SEA representatives (aggregate n = 35711) and -0.21 and 515 across the identified NWE nations (n = 34601). We sorted each nation’s/entity’s dataset into five SLP levels (utilizing PISA’s own criteria) and placed students into SLP levels based on an average of ten plausible values for each individual student). ANOVA results showed Taiwan, Japan, and Korea, (with some qualified evidence for SEA as a region) to have an inverse U-shaped relationship between SRA and SLP; Finland, and Iceland (along with modest evidence for NWE as a region) had a negative linear relationship between SRA and SLP. Multilevel modeling (MLM; within nations/entities only) partially confirmed our parallel ANOVA results: an inverse U-shaped relationship for Taiwan, and the negative linear relationship for Finland and Iceland. Our Belgian MLM also showed negative linearity. Thus, our results confirmed the earlier observation of an inverse U-shaped relationship between student anxiety measures and academic performance in Taiwan (extending that finding to a science context—and further extending that finding for science to Japan and Korea). We discuss possible classroom interventions aimed at mitigating nonadaptive anxieties among students at intermediate SLP levels.